Mental Health Projects for University Students: A Systematic Review of the Scientific Literature Available in Portuguese, English, and Spanish - Suyo-Vega, Josefina Amanda; Meneses-La-Riva, Monica Elisa; Fernández-Bedoya, Víctor Hugo; Polonia, Ana da Costa; Miotto, Angélica Inês; Alvarado-Suyo, Sofía Almendra; Ocupa-Cabrera, Hitler Giovanni; Alarcón-Martínez, Maricela (Frontiers in Sociology, 2022)
The mental health of college students has been the source of research, projects, and public policies involving education, health, and psychology professionals. Having as its axis the study of mental health and the phenomenon of psychological illness, this systematic review aims to characterize mental health programs directed to college students, as well as the forms of interventions offered to reduce the incidence of psychological disorders. From the proposal, a survey was conducted in the databases Scopus, Lilacs and the repository Alicia, in the period between 2010 and 2021, choosing the search phrase “Programas de saúde mental para universitários” in Portuguese, “Mental health projects for university students” in English, and “Proyectos en salud mental para estudiantes universitarios” in Spanish. The research areas spanned humanities and social sciences, with peer-reviewed and open access articles. The questions that instigated the study were as follows: What are the mental health problems affecting college students? What type of strategy has been adopted to map the demands of university students in relation to mental illness? How can the university space reorganize itself to work on interventional-preventive aspects, according to the studies? Initially, 740 203 articles were obtained, and after sifting through 13 productions, using the PRISMA systematization. Despite several researches interrelating mental health and university space, most were dedicated to data collection, using questionnaires, inventories, and scales, standardized and non-standardized. Only three studies described intervention projects and programs to reduce the problems of psychological distress in college students. Unanimously, the investigations emphasize the need for monitoring the higher education population regarding mental health and, in parallel, the implementation of institutional public policies to meet the students' demands and reduce the rates of problems in the educational field.